Nurse conditions psychological well-being in inpatient room hospital x - Rudy Dwi Laksono; Mulya Virgonita (Science Midwifery, 2023)
The purpose of this study was to determine the psychological well-being of nurses in the inpatient room of Hospital X. Because nurses often face high pressure, stress, and heavy workload. With improved nurse well-being, they can provide better healthcare to patients, closely correlate workforce retention, and impact productivity, job satisfaction, and overall performance. The population in this study was nurses in the inpatient room of Hospital X. This study used 6 dimensions of psychological well-being. This study used qualitative methods with a phenomenological approach of nurses in the inpatient room of Hospital X as participants who participated in this study. Data collection used in-depth interviews conducted directly with these participants. The results showed that all participants had psychological well-being influenced by each dimension. But in particular, it is known that there are two dimensions that most affect the psychological well-being of the nurses there, namely the dimension of positive relationships with others and the dimension of environmental mastery.